Mitochondrial Gene Expression of Three Different Dragonflies Under the Stress of Chlorpyrifos - Yuxin Chen; Ziwen Yang; Zhiqiang Guo; Lemei Zhan; Kenneth B. Storey; Danna Yu; Jiayong Zhang (Insects)
Chlorpyrifos (CPF) is an organophosphate insecticide that is extensively utilized globally due to its effectiveness against over 200 pest species. CPF exhibits its toxicity primarily through the inhibition of the acetylcholinesterase (AChE) enzyme, while mitochondrial damage and dysfunction have also been observed. The present study quantified the transcript levels of mitochondria protein-coding genes (mtPCGs) using quantitative real-time polymerase chain reaction (RT-qPCR) in samples of larvae of three dragonfly species (A. parthenope, E. elegans, and G. confluens) under different levels of CPF stress. By exposing larvae from uncontaminated populations to 0.05 μg/L CPF for 24 h, the transcript levels of seven mtPCGs in A. parthenope were significantly increased (p < 0.05) by 1.89 ± 0.42-fold for COI, 4.30 ± 0.24-fold for COIII, 5.94 ± 0.17-fold for ND1, 4.69 ± 0.56-fold for ND2, 3.44 ± 0.48-fold for ND4, 2.19 ± 0.53-fold for ND4L, and 5.05 ± 0.36-fold for Cytb, respectively. In E. elegans, the transcript levels of ND1, ND2, and ND4 increased by 1.23 ± 0.15, 1.48 ± 0.31, and 1.98 ± 0.25-fold, respectively (p < 0.05). In G. confluens, the transcript levels of COI, COIII, and ND4 increased by 1.56 ± 0.13, 1.50 ± 0.26, and 3.74 ± 0.40-fold, respectively (p < 0.01). It was demonstrated that the transcript levels of different mtPCGs showed significant up-regulation in the three different dragonfly larvae under CPF stress in the absence of mortality. ND4 was significantly increased in all three species, indicating that it is an important target gene. The present study underscores the response of mitochondrial gene expression in larvae of three different species in response to CPF pollutants, indicating that pesticide influences can potentially alter mitochondrial gene expression and potentially act as a method for assessing aquatic ecosystem health.